2003
DOI: 10.1103/physrevb.67.235204
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospectroscopy of Be in GaAs

Abstract: Far-infrared absorption measurements have been made of the Lyman series of the acceptor Be in GaAs up to magnetic fields of 30 T, supplemented by photothermal ionization spectroscopy measurements to 6 T. The results confirm and greatly extend previous work and reveal several phenomena. The strongest component of the G line moves to higher energies and increases in intensity with field. Around 20 T the field dependence of the transition displays a marked kink. At higher fields the dependence of energy on field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Only one of the samples shows a fine structure related to Lyman transitions of [Mn The three lines due to the transitions between ground 1S 3/2 and excited 2P states with different total momentum J, originating from different valence subbands (namely Γ 8 and Γ 7 ) are clearly seen. It is found that relative intensities of the lines are in agreement with those of the corresponding lines observed for shallow acceptors of GaAs [7,8].…”
Section: Experimental Details and Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Only one of the samples shows a fine structure related to Lyman transitions of [Mn The three lines due to the transitions between ground 1S 3/2 and excited 2P states with different total momentum J, originating from different valence subbands (namely Γ 8 and Γ 7 ) are clearly seen. It is found that relative intensities of the lines are in agreement with those of the corresponding lines observed for shallow acceptors of GaAs [7,8].…”
Section: Experimental Details and Resultssupporting
confidence: 75%
“…3 we plotted rescaled data for a typical shallow acceptor in GaAs, like carbon after Ref. [7] together with the results for [Mn 2+ (d 5 ) + a hole] center. As it is seen, the above--mentioned interaction amplifies the effect of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The energy differences between C and D lines (16.7 ± 1.5 cm −1 ), and G and D lines (31.8 ± 1.5 cm −1 ) are in good agreement with those theoretically predicted and experimentally observed for shallow acceptors in GaAs. 14,16,[18][19][20] The E b absorption peak at 203 ± 1 cm −1 (25.2 ± 0.2 meV) is attributed to a hole transition from the ground state to the continuum (top of the valence band) in the Lyman series and directly gives the acceptor binding energy. Since none of the binding energy values , 16 the observed absorption spectra ought to involve some different Bi-related acceptor state ∼25 meV above the valence band maximum.…”
mentioning
confidence: 99%
“…Schmitt et al, 11 in a theoretical study, propose a rule of thumb that the linear terms are adequate in describing the states to about B 0 * /5, or about 12 T in InP. However, it has been demonstrated in experiments in p-GaAs that the splittings of the magnetotransitions often follow a linear dependence to much higher fields and an explanation of that phenomenon given: 33 often the quadratic term is the same for the two excited states and so is eliminated if the difference is calculated. This allows accurate calculation of g factors using the linear approximation.…”
Section: Resultsmentioning
confidence: 99%